MicroRNA‐155 deficiency attenuates ischemia–reperfusion injury after liver transplantation in mice. (11th March 2015) - Tang, Bo; Wang, Zhenran; Qi, Guangying; Yuan, Shengguang; Yu, Shuiping; Li, Bo; Wei, Yangchao; Huang, Qi; Zhai, Run; He, Songqing
Summary Liver ischemia–reperfusion injury (IRI) is a major cause of morbidity and mortality after resection surgery, liver transplantation, and hemorrhagic and septic shock. Mir‐155 is upregulated by a broad range of inflammatory mediators, and it has been demonstrated to be involved in both innate and adaptive immune responses. However, the role of mir‐155 in liver IRI has never been investigated. In this study, mir‐155 deficiency protected mice from liver IRI, as shown by lower serum alanine aminotransferase (ALT) levels and Suzuki scores. Mir‐155 deficiency results in the development of M2 macrophages, which respond to IR‐induced innate immune stimulation by producing a regulatory inflammatory response with higher level of IL‐10, but lower levels of TNF‐α, IL‐6, and IL‐12p40. Mir‐155 deficiency suppresses IL‐17 expression, which contributes to the liver IRI development. In our further in vitro study, the results show that the Th17 differentiation is inhibited by SOCS1 overexpression and the promoted M2 macrophage development induced by mir‐155 deficiency is abolished by SOCS1 knockdown. In conclusion, mir‐155 deficiency attenuates liver IRI through upregulation of SOCS1, and this was associated with promoted M2 macrophage and inhibited Th17 differentiation.